Cooperative learning and its relationship with formative assessment in university students - Carbajal-Licas, Jenny; Brito-Garcías, José Gregorio; Flores-Cruz, Jesús Rule (Edelweiss Applied Science and Technology, 2025)
The aim of this research is to measure the relationship between formative assessment and cooperative learning in the classroom of a public university. This research is based on a hypothetical-deductive method, using a quantitative approach and a cross-sectional correlational design. The instruments used were questionnaires applied to a total of one hundred and fifty-eight students. The Kolmogorov–Smirnov test was applied to verify the assumption of normality, while Spearman’s rho was used for the correlation test. The results of the statistical analysis show a moderate positive relationship among the variables with a correlation coefficient of 0.619. The analysis highlights a moderate positive relationship between the positive interdependence dimension and formative assessment, as well as with the individual and group responsibility dimension. The study concluded that, to improve formative assessment, cooperative learning must prioritize communication skills along with pedagogical and reflective training of faculty members.